2004
DOI: 10.1111/j.1365-2958.2004.04283.x
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial cell division and the septal ring

Abstract: Cell division in bacteria is mediated by the septal ring, a collection of about a dozen (known) proteins that localize to the division site, where they direct assembly of the division septum. The foundation of the sep-tal ring is a polymer of the tubulin-like protein FtsZ. Recently, experiments using fluorescence recovery after photobleaching have revealed that the Z ring is extremely dynamic. FtsZ subunits exchange in and out of the ring on a time scale of seconds even while the overall morphology of the ring… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
205
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 206 publications
(208 citation statements)
references
References 86 publications
3
205
0
Order By: Relevance
“…Once assembled, the Z ring recruits several membrane-associated proteins that are essential for cell division 2 (FIG. 5).…”
Section: Ftsz Function In Bacteria Assembly Of the Cytokinesis Machinementioning
confidence: 99%
“…Once assembled, the Z ring recruits several membrane-associated proteins that are essential for cell division 2 (FIG. 5).…”
Section: Ftsz Function In Bacteria Assembly Of the Cytokinesis Machinementioning
confidence: 99%
“…It has been proposed that protein components of the cell division machinery could catalyze fission (Sharp and Pogliano 1999;Liu et al 2006;de Boer 2010;Fleming et al 2010). Alternatively, it has been suggested that cell wall synthesis on the outside of the cell could force the constricting membranes into close proximity, ultimately leading to fission (Weiss 2004;Judd et al 2005;Meyer et al 2010). To date, no protein has been directly implicated in this fission reaction.…”
mentioning
confidence: 99%
“…It is crucial that the two daughter nucleoids are segregated into each half of the cell, so that each daughter cell receives a copy of the genetic material and that none of the nucleoids are trapped in the septum. To ensure this, cell division and chromosome segregation are highly regulated processes involving a number of different proteins (see Egan & Vollmer, 2013;Harry et al, 2006;and Weiss, 2004, for reviews), the most studied being FtsZ. This protein polymerizes to form a ring-like structure at the site of division and serves as a scaffold for recruitment of other division proteins (Bi & Lutkenhaus, 1991).…”
Section: Introductionmentioning
confidence: 99%